Peningkatan Program Matrikulasi dan Membangun Karakter Siswa Melalui Pendekatan Inovatif - Parlindungan Sitorus; Julianti Sinaga; Mika Sinambela; Delverida Simanullang; Kharisma Dioi Handayani Siahaan (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This program is an activity carried out to improve the matriculation program and build student character through an innovative approach. This activity takes place every time after school and is carried out at the school in stages starting from class X and class XI. Apart from providing free matriculation tutoring, discussion time with students discusses assignments and meetings aimed at building character. This matriculation program is carried out by means of teaching and training by providing material and practice questions for each activity carried out. PkM activities are carried out at SMA N 4 Binjai from 14.30 WIB to 16.00 WIB every Monday to Thursday followed by Saturdays and the student character building program is carried out on Fridays and Saturdays twice a month during PkM. PKM with the title "Improving the Matriculation Program and Building Student Character Through an Innovative Approach" shows that through an innovative approach in the matriculation program, not only academic improvement occurs, but also the strengthening of student character. Learning not only improves understanding of concepts, but also forms students' creativity, critical thinking and social skills.